Women and Sports in Ancient Greece: Participation, Spectatorship and Cult in Olympia - Νικολούλη, Βασιλική (Πανεπιστήμιο Πελοποννήσου, 2012)
The aim of this paper is to present the position of women in the social life of ancient Greece during the Minoan, Mycenaean, (particularly) the archaic and classical, and Hellenistic times. The paper presents women who, due to their work and virtues, have excelled in various fields (science, literature, sports). It focuses on participation of women in athletic contests, which were organized in the context of religious festivals. Moreover, the paper studies the Heraia festival and the relationship of women to the corresponding male festival of the Olympic Games. The presence of women in the public life of the Greek state (polis) was limited, with the exception of Sparta, which indicates a different, more liberal attitude towards women. However there is fragmentary archaeological and literary evidence, that some women in ancient Greece managed to impose their presence on the social reality of their time, with courage, spirituality and talent, and managed to leave their name indelibly written in the pages of history.
Keywords: Women - Greece, Ancient - Religious life; Athletics for women - Greece, Ancient; Women - Greece, Ancient - Social aspects; Women - Greece, Ancient - History; Γυναίκες - Ελλάδα, Αρχαία - Θρησκευτική ζωή; Αθλητισμός για γυναίκες - Ελλάδα, Αρχαία; Γυναίκες - Ελλάδα, Αρχαία - Κοινωνικά θέματα; Γυναίκες - Ελλάδα, Αρχαία - Ιστορία